Dampak PDRB pada Sektor Pertanian, Nilai Tukar Petani, Investasi dan Area Lahan Pertanian pada Penyerapan Tenaga Kerja di Sektor Pertanian di Provinsi Jawa Tengah - Pujiyanto, Muhammad Aris (Fakultas Pertanian, Universitas Timor, 2024)
One of the important components in measuring the growth and sustainability of a country's economy is the absorption of labor. Central Java Province, which is known as one of the main agricultural centers in Indonesia, has many diverse variables that affect the absorption of labor in agriculture. This study investigates how the GDP of the agricultural sector, farmers' exchange rate, investment, and agricultural land area affect the absorption of labor in the agricultural sector of Central Java Province. This research method uses a quantitative approach with multiple regression analysis of secondary data collected from various sources from 2013-2023. The results of the analysis show that the GDP of the agricultural sector with a significance value of 0.025, the farmer exchange rate with a significance value of 0.000 and the area of agricultural land with a significance value of 0.000 have a significant influence on labor absorption, while investment with a significance value of 0.353 has no significant influence on labor absorption. Although not directly significant, investment also plays an important role in employment dynamics. This study shows that to improve people's welfare and strengthen the regional economy in Central Java Province, there is a need for policies that support agricultural economic growth, price stability of agricultural products, and investment development that focuses on the creation of direct jobs in the agricultural sector.